Mitochondrial DNA variability of the pipefish Syngnathus abaster. Issue 3 (6th February 2013) - Sanna, D.; Biagi, F.; Alaya, H. B.; Maltagliati, F.; Addis, A.; Romero, A.; De Juan, J.; Quignard, J.‐P.; Castelli, A.; Franzoi, P.; Torricelli, P.; Casu, M.; et al.
Abstract : This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish‐water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference (BI), maximum likelihood (ML) and network analyses, which were consistent in showing three well‐separated clusters of S. abaster populations. Furthermore, BI and ML did not support the monophyly of the taxon S. abaster . These results suggest the occurrence of a species complex in the study area, whose differentiation may have occurred since the Pleistocene. The results also show a very high genetic variability at the inter‐population level, with no shared haplotypes among sites. Evolutionary forces due to the fragmented nature of the brackish‐water habitats may account for the high genetic divergence found among the groups and populations. Finally, although dispersal by rafting over long distances may occasionally occur, this study suggests linear stepping‐stone model of colonization to be most likely. The complexity of the results obtained suggests that further studies are needed to elucidate the phylogeny of S. abaster .